Genetic variation of the mangrove species Avicennia marina in heavy metal polluted estuaries of Cilegon Industrial Area, Indonesia - JEPRIANTO MANURUNG; ISKANDAR Z. SIREGAR; CECEP KUSMANA; FIFI GUS DWIYANTI (Biodiversitas Journal of Biological Diversity, 2017)
Manurung J, Siregar IZ, Kusmana C, Dwiyanti FG. 2017. Genetic variation of the mangrove species Avicennia marina in heavy metal polluted estuaries of Cilegon Industrial Area, Indonesia. Biodiversitas 18: 1109-1115. Mangrove forests are often facing various anthropogenic disturbances, particularly in the industrial area. However, information on the status of industrial heavy metal pollution and its impact on the genetic variation of mangrove species, such as Avicennia marina, particularly in Indonesian industrial area has not been assessed. In this study, the classification of heavy metals in two estuaries of Cilegon Industrial Area (Pelabuhan Warna Sari and Krakatau) and one estuary outside Cilegon Industrial Area (Pulau Sangiang) were determined by Sediment Quality Guidelines- States Environment Protection Agency (SQGs-USEPA). Furthermore, the genetic diversity of 72 individuals of A. marina in the three estuaries were examined using four microsatellite loci (M3, M64, M81 and M98). The results showed that Krakatau area was the heavily polluted estuary based on SQGs-USEPA and have a lower genetic variation (He= 0.54) than Pelabuhan Warna Sari (moderately polluted, He= 0.56) and Pulau Sangiang (non-polluted, He= 0.60) suggesting a notable of deficiencies of genetic variation of A. marina in heavy polluted estuary compared to moderately and non-polluted estuary. Considering the low level of genetic variation in heavily polluted area, transplantation among estuaries and introduction of propagules from non-polluted estuary or other regions are needed as one of the conservation efforts.